Tablet diffusion, adoption and implementation in academic libraries: A qualitative content analysis of librarians’ discourse on blogging platforms - Scale, Mark-Shane E. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This study examines the evidence on blogs and tweets about the diffusion of tablets in academic libraries to find out why do early adopters or academic librarians adopt tablets and implement them into library services? Results reveal two factors why academic librarians and libraries adopt and integrate tablets. Cette étude examine les traces sur les blogues et les microbillets concernant la diffusion des tablettes dans les bibliothèques universitaires. L’objectif est de déterminer pourquoi les acheteurs précoces ou les bibliothécaires universitaires adoptent les tablettes et les intègrent dans leurs services en bibliothèque. Les résultats révèlent deux facteurs expliquant pourquoi les bibliothécaires universitaires et les bibliothèques adoptent et intègrent les tablettes.